Studi Hadis Larangan Menunda Shalat Karena Makan - Mei Yanti Azmi Hasibuan; Yulia Rahmi (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
Abstract. This research is motivated by the importance of prioritizing prayer compared to other activities. A hadith from Sunan Abu Dawud suggests that the Prophet did not allow prayers to be postponed because of food or other reasons. And this hadith seems to conflict with other more popular hadiths such as the authentic Bukhari hadith and the authentic Muslim hadith. In the hadith narrated, it has the same meaning, namely allowing to prioritize eating over prayer, but from the hadith of Jabir bin Abdullah, it appears to be inconsistent with other hadiths from Anas bin Malik and father. In the history of Jabir bin Abdullah, it appears that there was a prohibition on the Prophet to prioritize eating and other activities compared to others. with prayer. Meanwhile, Anas bin Malik and Aisyah are allowed to prioritize eating over praying. This research is library research. Library research is a research activity carried out by collecting data directly from libraries and books related to the problem to be researched directly. Meanwhile, the type of research used in this research is qualitative research using takhrij al-hadith, sanad criticism and hadith understanding methods. The results of this research, seen based on the analysis of the hadith writer from Jabir bin Abdullah, do not appear to be in line with other hadiths from Anas bin Malik and father. In the history of Jabir bin Abdullah, it can be seen that the Prophet's prohibition on prioritizing eating and other activities compared to prayer. Meanwhile, Anas bin Malik and Aisyah are allowed to prioritize eating over praying. The purpose of the hadith prohibiting delaying prayer is to prevent the makruh act of praying for people who are in a condition of hunger and other things because this clearly disturbs the sincerity of the heart.